2009
DOI: 10.1177/0192513x09339290
|View full text |Cite
|
Sign up to set email alerts
|

Just Doing What They Gotta Do

Abstract: For single african american custodial fathers, parenting stress is exacerbated by the cultural expectation that Black fathers are "normally" absent and by the clustering of stresses that Black men are more likely to encounter. This sample of african american fathers have used a repertoire of problemfocused and cognitive coping strategies, including some that are frequently considered "culturally specific." Twenty Black single custodial fathers are interviewed and their narratives are analyzed for concepts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…This mirrors the experience of fathers in other contexts who often feel excluded or judged when using prenatal services (Coles 2009;Ross et al 2012;Steen et al 2012). In their review of men's experiences of maternity care, Steen et al (2012) conclude that fathers cannot effectively support their partner during pregnancy and early parenting if they themselves are not supported.…”
Section: Inclusion Of Fathers In Perinatal Services: a Call For Separate Programmingmentioning
confidence: 83%
See 1 more Smart Citation
“…This mirrors the experience of fathers in other contexts who often feel excluded or judged when using prenatal services (Coles 2009;Ross et al 2012;Steen et al 2012). In their review of men's experiences of maternity care, Steen et al (2012) conclude that fathers cannot effectively support their partner during pregnancy and early parenting if they themselves are not supported.…”
Section: Inclusion Of Fathers In Perinatal Services: a Call For Separate Programmingmentioning
confidence: 83%
“…Excluding fathers who may be considered risky without first offering comprehensive targeted support denies them an important opportunity to change, and denies their children a better chance to grow up with a healthy relationship with their fathers (Coles 2009). Yet the inclusion of fathers in programming for families with experiences of violence is not and will not be simple.…”
Section: Inclusion Of Fathers In Perinatal Services: a Call For Separate Programmingmentioning
confidence: 99%
“…Another strength of the study is the focus on various sources of support. As previously mentioned, many studies on social support often aggregate support dimensions (Castillo & Sarver, 2012; Coles, 2009; DeGarmo et al, 2008), making it difficult to understand within‐group variation among sources of social support. Utilizing a latent profile approach deepens our understanding of how the various dimensions work together within a real‐life context.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the research has found that Black men note sources of support that are used to combat family‐ and parenting‐related stressors. Beyond the general function of social support, however, studies indicate that fathers often desire social support to help navigate the day‐to‐day challenges of fathering (Coles, 2009; Doyle et al, 2014). Largely, the literature has highlighted co‐parenting relationships and romantic partnerships (Doyle et al, 2014; Perry et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation